Use of pade aproximation for e-z to approximate an integral of a Bessel function - Luke, Yudell (Rev. Téc. Fac. Ing. Univ. Zulia)
In a number of my previous works, I have emphasized a global approach to the approximation of functions. Numerical values of a function are but a facet of the overall problem. We desire approximations to evaluate functions and their zeros, to simplify transforms and their inverses, and to facilitate the direct solution of various functional Equations, In this paper, we illustrate our ideas by using Padé approximations for the exponential function to evaluate integral involving the Bessel function I0(z)